Efficacy of Sertraline Combined with Cognitive Behavioral Therapy for Adolescent Depression: A Systematic Review and Meta-Analysis. (28th December 2021) - Liu, Wenliang; Li, Gongying; Wang, Congjie; Wang, Xiuzhen; Yang, Lin
Abstract : Objective . The efficacy of antidepressant drugs combined with psychotherapy is controversial; hence, this meta-analysis was conducted to assess the efficacy of the combination therapy. Methods. Relevant literature was searched in PubMed, Web of Science and Embase, Chinese databases CNKI, and WanFang Data. We included the literature on the comparison of the sertraline combined with cognitive behavioral therapy (CBT) and each treatment alone for adolescent depression published in 2000-2021. Meta-analysis was performed using Stata16.0 software. Results. A total of 421 relevant articles were retrieved, and 14 studies were finally included. In comparison with the control group (sertraline), sertraline combined with CBT achieved higher response rate (OR = 5.07, 95% CI: 3.00, 8.58) and lower incidence of adverse reactions (OR = 0.43, 95% CI: 0.24, 0.75). Before treatment, there were no significant differences in depression score, anxiety score, and symptom self-rating scale score between the two groups. After treatment, depression score (SMD = − 2.79, 95% CI: -3.64, -1.94), anxiety score (SMD = − 1.22, 95% CI: -1.96, -0.47), and symptom self-rating scale score (SMD = − 1.73, 95% CI: -3.19, -0.27) were significantly lower in the combined treatment group than in the control group. Conclusion. Although the number of comparative trials is small, this study shows that sertraline is effective for adolescent depression, but sertraline combined with CBT is more effective. The latter can significantly reduce the incidence of depressive symptoms, anxiety, and adverse reactions in patients. Therefore, this combination therapy is recommended for the clinical treatment of adolescent depression.